2011
DOI: 10.1002/mus.22043
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cranial neuropathy variant of guillain–barré syndrome: A case series

Abstract: Bilateral CN IX, X, and/or VII impairment with areflexia or hyporeflexia, early abnormal F-wave response, nerve conduction abnormalities, and CSF albuminocytologic dissociation support a diagnosis of this GBS cranial variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 23 publications
(30 reference statements)
1
24
0
Order By: Relevance
“…Furthermore, cases of cranial neuropathy involving only the glossopharyngeal nerve and vagus nerve, in addition to bilateral facial palsies, have been reported as a pharyngo-facial variant (12) or multiple cranial neuropathy variant (13). Several cases of cranial neuropathy associated with glossopharyngeal nerve and vagus nerve palsies alone have also been reported (14). These studies reported the rapid improvement of symptoms in such cases following treatment with IVIg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cases of cranial neuropathy involving only the glossopharyngeal nerve and vagus nerve, in addition to bilateral facial palsies, have been reported as a pharyngo-facial variant (12) or multiple cranial neuropathy variant (13). Several cases of cranial neuropathy associated with glossopharyngeal nerve and vagus nerve palsies alone have also been reported (14). These studies reported the rapid improvement of symptoms in such cases following treatment with IVIg.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patient's rapid recovery from dysphagia and dysarthria following IVIg treatment strongly suggests the presence of primarily demyelinating lesions. Cases of the cranial neuropathy variant type GBS with normal nerve conduction velocity (NCV) results in the limbs have also been reported (14).…”
Section: Discussionmentioning
confidence: 99%
“…Several variants of Guillain-Barré syndrome with involvement of cranial nerves have been described. However, multiple involvement of cranial nerves without motor de cit in limbs is extremely rare, affecting only 5% of all the cases reported in the literature [4][5] . Recently, Gutierrez-Ortiz and coworkers reported two cases of Miller Fisher syndrome and polyneuritis cranialis in COVID 19, yet they did not perform MRI and neurophysiology 2 .…”
Section: Casementioning
confidence: 99%
“…Numerous variants of Guillain-Barre syndrome (GBS) have been documented during the past decade [ 1 , 2 ]. These variants have similar symptoms and developmental, recovery, and treatment patterns.…”
Section: Introductionmentioning
confidence: 99%
“…These variants have similar symptoms and developmental, recovery, and treatment patterns. Cranial nerve (CN) palsies are common symptoms of GBS, but multiple cranial neuropathies as variant of GBS are rare and account for only 5% of patients [ 2 ]. Affected patients exhibit bilateral facial nerve palsy followed by bulbar dysfunctions (CN IX and X) with limb weakness and walking difficulties [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%